ALGORITHMS AND METHODS OF AUTOMATIC CONTROL OF LIGHTING SYSTEMS OPTICAL CHARACTERISTICS - V. I. Kornaga; O. S. Oliinyk; V. M. Sorokin; A. V. Rybalochka (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The prototype of lighting system and algorithms of automatic control of its optical parameters was developed. The results of the research of autoregulation colour temperature algorithms and brightness of the light were shown.